Problematika Kebijakan Dana Hibah dan Bantuan Sosial Sumber APBD: Relasi Korupsi Terhadap Kekuasaan Kepemimpinan, dan Perilaku Elit - Wimmy Haliim (Inovasi, 2020)
This study tries to inform readers that the problematic of grants and social assistance programs has a high vulnerability to corruption and political interests. This study is a normative research with a conceptual approach, because this research is a study that combines the discussion of political science and public administration to explain a phenomenon. First is the Relationship of Power and Corruption. Second is moral and political leadership in corrupt practices. Third is the problem of elite behavior, bureaucracy and a culture of corruption in the regions. The purpose of this article is to provide a requirement for the State to oversee and oversee the implementation of grants and social assistance policies. Public control is also needed not only to ensure that both grants and social assistance are properly realized and on target, but also avoids the implementation of problems of corruption and the political interests of certain elites. Keywords: grants fund, social assistance, policy, elite, bureaucracy, corruption